A shell formulation for fibrous reinforcement forming simulations. (September 2017) - Liang, B.; Colmars, J.; Boisse, P.
Abstract: The fibrous nature of continuous fiber textile composite reinforcements strongly modifies their mechanical behavior, in particular for bending. The basic assumptions of classical plate and shell theories are not verified by these materials during a deformation because of the slippage between fibers. However, simulations of reinforcement forming generally use shell finite elements. A shell formulation is proposed for the forming of continuous fiber reinforcements. The large tensile stiffness leads to the quasi inextensibility in the fiber directions. The fiber bending stiffness determines the curvature of the reinforcement. The calculation of tensile and bending virtual works are based on the precise geometry of the single fiber. A simple way to consider friction between fibers is to take it into account in the flexion bending. Simulations and experiments are compared for different reinforcements. It is shown that the proposed fibrous shell approach not only correctly simulates the deflections but also the rotations of the through thickness material vectors. This is particularly interesting in the case of thick interlock reinforcements.